Does lysine level fed in one phase influence performance during another phase in nursery pigs? - Nemechek, J.E.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 320 weanling pigs (PIC 1050 barrows, initially 12.6 lb and 21 d of age) were used in a 35-d trial to determine whether the lysine level fed during 1 phase in the nursery influences the response to dietary lysine during another phase. Eight dietary treatments were allotted and arranged as a 2 × 2 × 2 factorial, with 5 pigs per pen and 8 pens per treatment. Diets were fed in 3 phases, with each treatment assigned as low or normal lysine level. Standardized ileal digestible lysine levels were 1.35 vs 1.55% during Phase 1 (d 0 to 7), 1.15 vs 1.35% in Phase 2 (d 7 to 21), and 1.05 vs 1.25% during Phase 3 (d 21 to 35). Pigs and feeders were weighed on d 0, 7, 14, 21, 28, and 35 after weaning to calculate ADG, ADFI, and F/G. There were no dietary interactions between phases (P > 0.10). From d 0 to 7, increasing dietary lysine did not influence (P > 0.10) ADG (0.35 vs 0.35 lb/d) or ADFI (0.36 vs 0.33 lb/d), but improved (P < 0.005) F/G (1.06 vs 0.97). With results similar to those of Phase 1, increasing dietary lysine from d 7 to 21 did not influence (P > 0.10) ADG (0.78 vs 0.82 lb/d) or ADFI (1.15 vs 1.13 lb/d), but improved (P < 0.03) F/G (1.48 vs 1.39). From d 21 to 35, increasing dietary lysine improved (P < 0.001) ADG (1.23 vs 1.32 lb/d) and F/G (1.64 vs 1.54). These results indicate that lysine level fed in each phase did not influence the response to lysine in the subsequent phase. The lysine level fed during the late nursery phase had a greater effect on overall performance than the level fed in earlier phases.
Keywords: Swine; Lysine; Phase feeding; Requirement